Disidencias feministas en la Iglesia católica mexicana: el movimiento para la ordenación de mujeres durante los setenta del siglo XX - Espino Armendáriz, Saúl (El Colegio de México, A.C., 2022)
This article documents and analyzes the feminist dissidence within the Mexican Catholic Church in the 1970s, focusing on the movement for the ordination of women. It studies the movement’s Catholic roots and activist networks, showing the leading role played by the groups in Cuernavaca (Morelos, Mexico) that were centered around Betsie Hollants, the dialogue and exchange with activists from the United States and the ideological tensions of a transnational movement in the polarized context of the Cold War. This article’s historical window for analyzing Catholic feminism is the planning, founding and early years of the Mujeres para el Diálogo group and its sources include correspondence, memoirs, minutes, books, newspapers and magazines held by public and private archives in Mexico and the United States.